FSH status in normal and obese individuals - S, AISHWARYA; ROY, DR. ANITHA; DR.T. LAKSHMI , (The journal of contemporary issues in business and government, 2021)
Obesity is one of the major and common health problems in all developed and developing countries leading to infertility. It also acts as an important modifier of reproductive hormones. Follicle-stimulating hormone (FSH), a pituitary-derived glycoprotein hormone, is associated in reproductive activities such as formation of gonadal and germ cells and the development of sex hormones. The goal of this study was to assess the FSH level in normal and obese individuals. 60 subjects were chosen from those attending the outpatient department of a private hospital and divided into two groups (n=30). Group1 served as control having healthy individuals, Group 2 served as study group with obese individuals. 5 ml of venous blood was collected from the participants after informed consent and was centrifuged at 2500 rpm for 10 minutes. The serum was separated and analysed for serum FSH by standard enzyme linked immunosorbent assay technology (ELISA) using Robonik Elisa reader. The mean BMI levels between the groups were 21.98±2.59 and 34.42±3.82 respectively. The mean FSH levels between the groups were 10.43±4.43 and 5.59±2.53respectively. These results were analysed by student t- test and showed significant difference between these two groups (p <0.0001). Obese individuals had low FSH levels, when compared to the normal healthy individuals. The findings clearly indicate that there is an association between obesity and hormone changes in individuals.